2022
DOI: 10.21203/rs.3.rs-2264630/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Escherichia coli cells are primed for survival before lethal antibiotic stress

Abstract: Non-genetic factors can cause significant fluctuations in gene expression levels. Regardless of growing in a stable environment, this fluctuation leads to cell-to-cell variability in an isogenic population. This phenotypic heterogeneity allows a tiny subset of bacterial cells in a population, referred to as persister cells, to tolerate long-term lethal antibiotic effects by entering into a non-dividing, metabolically altered state. One fundamental question is whether this heterogeneous persister population is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 58 publications
5
23
0
Order By: Relevance
“…However, we believe that the true potential of this generalized fluctuation test is in microbial systems, where (unlike mammalian cells) cells are readily grown from single cells with relatively fast doubling times, and there is a longstanding tradition of performing the Luria–Delbrück experiment. Working in this direction, we currently have several ongoing collaborations probing antibiotic tolerance across bacterial species ( Mycobacterium tuberculosis, Vibrio cholerae, Enterobacter cloacae , and Salmonella enterica ), and a recent study characterizes the transient priming of bacterial cells even before lethal antibiotic stress (Hossain et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that the true potential of this generalized fluctuation test is in microbial systems, where (unlike mammalian cells) cells are readily grown from single cells with relatively fast doubling times, and there is a longstanding tradition of performing the Luria–Delbrück experiment. Working in this direction, we currently have several ongoing collaborations probing antibiotic tolerance across bacterial species ( Mycobacterium tuberculosis, Vibrio cholerae, Enterobacter cloacae , and Salmonella enterica ), and a recent study characterizes the transient priming of bacterial cells even before lethal antibiotic stress (Hossain et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Persister assay. The assay was done as previously described 11,24 . Briefly, overnight cultures were diluted 1/100 into fresh media and grown until they reached between OD 600 ~0.1-0.2.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent work reveals that high persistence levels do not correlate with high short-term tolerance levels. Hence, it becomes imperative to use lethal antibiotic concentrations when investigating the transcriptional regulatory mechanisms of persisters 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that stochastic expression of specific proteins can lead to resistance to drug therapy arising transiently. In such case, cells switch to become resistant for several generations, but then switch back into a drug-sensitive state [2][3][4][5][6]. Several tools that exploit the colony-to-colony variation to estimate the rates of switching into and out of the resistant state have been recently developed [7,8].…”
Section: Introductionmentioning
confidence: 99%